A REVIEW ON THE PROBABLE MODE OF ACTION OF HINGUVACHADI CHURNA (POWDER)- AN AYURVEDIC FORMULATION WITH MULTIFACETED ACTION - Sinimol.T.P,; Emy. S.Surendran,; Varsha Sumedhan,; Meghna.P.P,; V.Subhose, (International Journal of Ayurveda and Pharma Research, 2021)
Since time immemorial, a wide variety of various formulations have been used by Ayurvedic physicians to treat different gastro intestinal disorders which includes Churna (powder), Kwatha (decoctions), fermented preparations like Asava and Arishta, Lehya (linctus), Vati/ Gutika (tablets) etc. Agnimandya (slow digestive power) is considered as the root cause of all disorders in Ayurveda, especially gastrointestinal disorders. Hinguvachadi Churna is a time tested formulation widely used by Ayurvedic practitioners for correcting the digestive power of our body. There are 24 constituents in this formulation and is indicated in the management of certain specific disease conditions originated because of Vata and Kapha humour. Modern scientific world always need explanations and logic behind the mode of action of various Ayurvedic procedures. This review is an attempt to explain the mode of action of this formulation. On analysing the properties of the ingredients, it was found that it is predominant of Katu rasa (pungent taste), Ruksha (dry) Teekshna (sharp) Guna (property), Ushna veerya (hot potency), Katu vipaka (pungent taste after bio transformation). These properties are responsible for the various pharmacological action of the formulation in Ayurvedic terms. As per modern pharmacology, phytoconstituents of many herbs are having action concerned with motility and secretions of Gastrointestinal tract, ultimately resulting in improved digestive capacity of our body. Analysis of mode of action gives a deep insight about the usage of formulations with a better understanding. The physician can apply his logic to use the medicine in contexts other than indicated.